Familie Habsburg 1273-1918 - MacGuigan, Dorothy Gies, -1982 (München : Almathea Verlag, 1966)
Der gröszte Hader aller Zeiten - Papst gegen Kaiser - Avignon gegen Rom - Kaiser, Stadt und Dom
Vertaald uit het Engels